The perception and value of the new local language variety: the case of the Samogitians of periphery - Triaušytė, Monika (Lietuvių kalba, 2020)
Dialects change, transform, and new ones – transitional, intermediate varieties between dialect(s) and standard language – emerge due to various extralinguistic factors (see Lenz 2010, 296). The research shows that the variety of the periphery of Samogitia, Akmenė region has also changed (Murinienė 2018).The aim of this study is to reveal the gymnasium students’ competence to identify local intermediate variety by assessing it from the perspective of three language varieties – dialect, semi-dialect (intermediate variety) and standard language, and also its value. The data was obtained from a questionnaire, based on the methodological principles of sociolinguistics and perceptual dialectology, to reveal attitudes of young residents of Akmenė region.The analysis shows that gymnasium students, according to their verbalised and visualised attitudes, identify the local variety as a semi-dialect and reflect a less marked dialect. Respondents call it semi-Samogitian dialect, semi-Samogitian and semi-Highland dialect/standard language. In the mental maps, the local dialect is also marked as a semi-dialect and is located between Šiauliai and Mažeikiai, which reveals the reflected peripherality of the local language variety.According to the associations with users of semi-dialect, this variety acquires a high value compared to the (traditional) dialect. The user of the intermediate language variety is described as adaptable, flexible, and simultaneously modern, but not the person who abandons the traditions. The local language variety is important for expressing the local identity because the standard language usage is not recognised among the local dialect users as a conscious separation from the community if it is used in informal situations.
Keywords: the Samogitian of periphery; the intermediate variety; the conscious attitudes; the semi Samogitian dialect